Social Media Communications for African Public Institutions - Ms Ali, Aisha (CLEAR-AA, 2019)
Social media is growing exponentially in Africa. While many governments perceive an increase in political social media as a threat, and several governments have set up social media controls and even sanctioned complete blackouts in moments of heightened political tension, they are also increasingly finding it convenient to interact with their publics through social media. While this is mostly one-way broadcast-style communication about service delivery or in emergencies, the two-way, interactive possibilities of social media offer public institutions opportunities to tap into information from citizens and to interact.
Keywords: Social media, public institutions, digital era